The Impact of Behavioural Biases on Stock Volatility: Evidence From Pakistan Stock Exchange - IRFAN ULLAH; DR. MUHAMMAD ZAHID; ZAIN ULLAH (Journal of Business & Tourism, 2021)
The main purpose of the current study is to investigate the impact of behavioural biases such as confidence, optimism, and pessimism on stock volatility evidence from Pakistan Stock Exchange (PSX). Prospect theory and overconfidence theory formed the foundation of this study. The methodology composed of positivist philosophical stance, deductive approach and quantitative methods with secondary data. Data analysis involved the use of descriptive statistics, correlation and regression. The study consists ofa 10-years analysis from June 2008 to June 2018 and includes daily trading volumes KSE-100 index in PSX. Results reveal that behavioral biases such as confidence have a positive impact on stock volatility. Similarly, optimism bias has also a positive impact on stock volatility. While pessimism bias has recorded a negative impact on stock volatility. Therefore, it is concluded that behavioural biases have an impact on stock volatility. The current study has a contribution to the body of knowledge on the ground that it attempts to change the traditional notion of society who believes in the efficient market hypothesis. The study has implications for different stakeholders of stock markets.